Technicity and Publicness: Steps towards an Urban Space - Stephen Read (Footprint)
Heidegger’s space, with its emphasis on the disclosure of entities in settings of mutually referring entities, and the integration of settings and action, requires us to think carefully about issues like the identities and being of people and things and their relations with each other in a realm of plurality. All entities are captured in webs of co-reference, which make their relations between themselves and to ourselves a very public matter. These webs themselves are at the same time the very channels by which we know and access all things, and relations of power become built into them which affect the ways we know things and the possibilities we see for acting. This paper explores and reviews issues of technicity, intersubjectivity, and plurality in relation to Heidegger’s thinking, in order to begin the process of outlining an urban space of the settings ‘between men’ for coherence and action, and to define a direction for further research on urban space and place.